Is Cancer Solvable? Towards Efficient and Ethical Biomedical Science. Issue 3 (September 2019) - Shrager, Jeff; Shapiro, Mark; Hoos, William
Global Cumulative Treatment Analysis (GCTA) is a novel clinical research model combining expert knowledge, and treatment coordination based upon global information-gain, to treat every patient optimally while efficiently searching the vast space that is the realm of cancer research.